Өмнөд Монголын Герциний бүсийн геологийн формацын изотопын бүтэц - Г. Ээнжин; В.В. Ярмолюк; М.А. Козловский; Ц.Оюунчимэг (Geological Issues, 2023)
In the centre of hercynic of southern Mongolia siliceous volcanics, volcanic, shale-volcanic, flish and 5 main formations of volcanic molass have been extracted from the lithological composition and organic remains. By the last dates of geology, geochronology, geochemical and Nd-izotopic analyses have been revealed that Altai Chandakhi Desert, Edrengiin range, Sumankhairkhany range, and in south part of Gobi Altai range the hercynics main formation are continuing. Also determined of southern Mongolian of hercynic juvenile crust of geological formations of the isotopic composition. The isotopic composition of hercynic of southern Mongolia consists of the island arcs during Devonian and Silurian (about 420 million years), deep-water grooves and marine sediments. Island arc complex was formed in subduction zones with convergent boundaries. The hercynic rock crust activated during the late Mesozoic period by the accretion processes around of 350-120 million years penetrated from magmatic processes. In this case the continental crust of acidic rocks was formed from anatectite magma. Based on this study can be concluded that the hercynic juvenile crust of southern Mongolian has clear isotopic zones.